2022
DOI: 10.3389/fcimb.2022.870296
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Transplant Platelet Refractoriness and Alternative Donors Are Associated With Cytomegalovirus Retinitis in Hematopoietic Stem Cell Transplantation for Severe Aplastic Anemia

Abstract: BackgroundCytomegalovirus retinitis is a severe, vision-threatening opportunistic infection in an immunodeficient population. Reports on cytomegalovirus retinitis in hematopoietic stem cell transplant recipients due to severe aplastic anemia have been scant. This study assessed the risk of cytomegalovirus retinitis in relation to the pre-transplant status of severe aplastic anemia patients.MethodsWe conducted a retrospective nested case-control study of cytomegalovirus retinitis among severe aplastic anemia pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…We suspect that there was a low incidence of GVHD in our CMVR patients because all SAA recipients received ATG-based conditioning. Our group recently reported the pre-transplant risk factors for CMVR in SAA HSCT recipients ( Zhang et al., 2022 ). We found that if a SAA patient ready for HSCT had a history of platelet refractoriness before transplantation or had only alternative donors available, the risk of CMVR after HSCT would increase.…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that there was a low incidence of GVHD in our CMVR patients because all SAA recipients received ATG-based conditioning. Our group recently reported the pre-transplant risk factors for CMVR in SAA HSCT recipients ( Zhang et al., 2022 ). We found that if a SAA patient ready for HSCT had a history of platelet refractoriness before transplantation or had only alternative donors available, the risk of CMVR after HSCT would increase.…”
Section: Discussionmentioning
confidence: 99%